The role of civil society organizations in China and Germany: papers presented at the German-Chinese workshop in Beijing, March 13-15, 2009 - Freie Universität Berlin, Center for Global Politics (2009)
Abstract: From March 13 to 15, 2009, the Center for Global Politics at Freie Universität Berlin and the Chinese Center for Comparative Politics and Economics in Beijing held the workshop "The Role of Civil Society Organizations in China and Germany", funded by the Fritz Thyssen Foundation. The research objective was to analyze the role of civil society organizations in political regulation in China and Germany as well as their contribution to ensuring efficiency in specific policy areas. (author's abstract)